Perception of industries santa catarina managers on the factors strategy, organizational structure and uncertainty with environmental management control system (Revista Brasileira de Contabilidade e Gestão, 2016)
The objective of the study is to identify the perception of managers of Santa Catarina industries on factors strategy, organizational structure and environmental uncertainty with the management control system. Thus, there was a descriptive research, survey and quantitative approach. Data collection occurred through a questionnaire with closed questions, adapted from the study Jokipii (2010). The questionnaire took place in October 2014 and was made available in electronic format for the high escalation managers and members who could play the roles of managers, directors and supervisors. The population consists of all industries in the State of Santa Catarina, associated to the Federation of Industries of the State of Santa Catarina (FIESC). The sample comprised 11 respondents of the questionnaire applied. The results show that as the strategy, most agreed that was quickly resolved when something unusual happened to the controls. As for the organizational structure, most agreed that the responsibilities are described and disseminated, there are routines for new employees who demonstrate commitment and comply with their duties. As for the environmental uncertainty, most predict changes in the economic environment, needs and market activities of competitors.
Keywords: management control system; strategy; organizational structure; environmental uncertainty